1998
DOI: 10.1088/0963-0252/7/1/009
|View full text |Cite
|
Sign up to set email alerts
|

Helicon wave excitation with rotating antenna fields

Abstract: By using phased bifilar antennas, helicon waves have been excited by applying fields which rotate either in space or in time, or both simultaneously. The direction of rotation is made to favor either m = +1 or m = -1 waves, where m is the azimuthal mode number, and m is measured directly. Rotation in time is found to be more effective than rotation in space and makes possible a direct comparison of m = ±1 excitation. An m = -1 structure was seen only in the antenna near-field, while m = +1 modes propagate far … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
42
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 22 publications
7
42
0
Order By: Relevance
“…Apparently, the end rings have an appreciable effect on the antenna spectrum. The two antennaes' end rings differ not only by their separation, but also in the relative direction of the currents in them [12]. Surprisingly, the P (k) spectra of FW and HW antennae of the same length are similar in shape, with the FW spectrum higher; the pitch of the winding does not appear to matter.…”
Section: Computationsmentioning
confidence: 88%
See 1 more Smart Citation
“…Apparently, the end rings have an appreciable effect on the antenna spectrum. The two antennaes' end rings differ not only by their separation, but also in the relative direction of the currents in them [12]. Surprisingly, the P (k) spectra of FW and HW antennae of the same length are similar in shape, with the FW spectrum higher; the pitch of the winding does not appear to matter.…”
Section: Computationsmentioning
confidence: 88%
“…Other types include single-loop antennae [5][6][7], doubleloop antennae [8], double half-turn antennae [9], quadrupole antennae [10], solenoid antennae [11], and bifilar rotating-field antennae [12]. Relative efficiencies of these designs have been compared by several groups [12][13][14][15] and in general the results agree with calculations [16][17][18][19]. In this paper, we compare helical antennae of different lengths and find surprising results that appear to disagree with theory.…”
Section: Introductionmentioning
confidence: 99%
“…For helicons, the RH wave has higher amplitude at the boundary, thus coupling strongly to the TG wave. Studies of antennas 12 have shown that a helical antenna with the same helicity as the RH wave exhibits the best coupling. This is however not optimum for remote plasma, as shown in Fig.…”
Section: Array Sources and Antenna Designmentioning
confidence: 99%
“…Both antennas were 10 cm long, an optimal length found in previous tests [3,13]. As shown in figure 1, a right-helical antenna was positioned at the pump end, and a left-helical antenna at the opposite end, with B 0 in the +z direction (away from the pump).…”
Section: Apparatusmentioning
confidence: 99%